2012
DOI: 10.1007/s13730-012-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of secondary focal segmental glomerulosclerosis associated with malignant hypertension

Abstract: Focal segmental glomerulosclerosis (FSGS) is associated with various clinicopathological conditions, including hypertension. We report here a case of secondary FSGS associated with malignant hypertension. A 33-yearold man with a 1-month history of visual impairment and headache visited the Department of Ophthalmology at our hospital and was found to have hypertensive retinopathy and severe hypertension (230/160 mmHg). He was referred to our department based on suspected renal dysfunction. His blood pressure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…234 The concomitant finding of FSGS and TMA has been reported in four patients. In two patients, this was associated with malignant hypertension, 71,235 and in the other two cases TMA was felt to be druginduced 236,237 Two case reports describe the association of TMA and MN. 167,168 While a disease-enhancing role for complement has been generally accepted, the recent discovery of MN-specific autoantibodies to phospholipase A2 receptor (PLA2R), introduce a specific CP initiated role for the complement system in MN pathogenesis.…”
Section: Other Glomerulopathiesmentioning
confidence: 99%
“…234 The concomitant finding of FSGS and TMA has been reported in four patients. In two patients, this was associated with malignant hypertension, 71,235 and in the other two cases TMA was felt to be druginduced 236,237 Two case reports describe the association of TMA and MN. 167,168 While a disease-enhancing role for complement has been generally accepted, the recent discovery of MN-specific autoantibodies to phospholipase A2 receptor (PLA2R), introduce a specific CP initiated role for the complement system in MN pathogenesis.…”
Section: Other Glomerulopathiesmentioning
confidence: 99%
“…[10][11][12] In native kidneys, TMA-CG has only been anecdotally described in case reports or small series in conjunction with calcineurin inhibitors-related arteriolopathy, 13 sickle-cell disease, 14 antivascular endothelial growth factor (anti-VEGF) therapy-associated TMA, 15 mixed connective tissue disease-associated TMA, 16 or malignant hypertension. 17 The question of the prevalence and significance of CG changes in the setting of histological TMA has never been addressed in an unselected fashion, using native renal biopsy specimens. The purpose of our study was to explore the prevalence of CG in TMA, its clinicopathologic features, and the outcome of TMA-CG in native kidneys.…”
mentioning
confidence: 99%
“…Podocyte is major source of vascular endothelial growth factor (VEGF), and anti-VEGF antibody, anti-VEGF ligand, and receptor tyrosine kinase inhibitors similarly caused heavy proteinuria with TMA and FSGS lesions [ 30 , 31 ]. Several reports described the overlap between disorders with endothelial damage and histological FSGS: Preeclampsia [ 32 ], TMA induced by malignant hypertension [ 33 ] or reno-vascular hypertension [ 34 ]. A retrospective study showed that FSGS, particularly COL, was commonly (62.3%) observed among cases with TMA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%